Pengembangan Bahan Ajar Komik Siswa di Kelas 3 pada Tema 2 di SDN Tlogi Blitar - Aghitsatul Habibah; Arina Restian; Murtyas Galuh Danawati; Alfani Athma Putri Rosyadi (Universitas Indraprasta PGRI Jakarta, 2021)
The purpose of this study was to describe the results of developing Sahabat comics teaching materials for grade 3 students at SDN Tlogo 02 Blitar. This development research uses the ADDIE model. The ADDIE development model consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The data analysis techniques were qualitative data analysis techniques and quantitative data analysis techniques with the aim of knowing how to develop the feasibility of E-Comic teaching materials for students in grade 3 on theme 2 SDN Tlogo 02 Blitar. In the analysis, the researcher conducted an assessment of theory and material, at the design stage the researcher compiled Sahabat comic, at the development and implementation stage the researcher applied the comic results that had been compiled, at the evaluation stage, the researcher reflected on the results that had been obtained after the application of the comic. Sahabat comic teaching materials for grade 3 students of SDN Tlogo 02 get a percentage value of 81.8 valid learning materials according to revision. Validation of teaching materials is 91.6% with proper qualifications without revision, student responsed to Sahabat comics get a percentage of 99.5% indicating that Sahabat comics is very worth it.